Clinical Response to Vedolizumab in Ulcerative Colitis Patients Is Associated with Changes in Integrin Expression Profiles - Fuchs, Friederike; Schillinger, Daniela; Atreya, Raja; Hirschmann, Simon; Fischer, Sarah; Neufert, Clemens; Atreya, Imke; Neurath, Markus F.; Zundler, Sebastian (Frontiers in Immunology, 2017)
Background: Despite large clinical success, deeper insights into the immunological effects of vedolizumab therapy for inflammatory bowel diseases (IBD) are scarce. In particular, the reasons for differential clinical response in individual patients, the precise impact on the equilibrium of integrin-expressing T cell subsets and possible associations between these issues are not clear. Methods: Blood samples from patients receiving clinical vedolizumab therapy were sequentially collected and analyzed for expression of integrins and chemokine receptors on T cells. Moreover, clinical and laboratory data from the patients were collected and changes between homing marker expression and clinical parameters were analyzed for possible correlations. Results: While no significant correlation of changes in integrin expression and changes in outcome parameters were identified in Crohn’s disease (CD), increasing α4β7 levels in ulcerative colitis (UC) seemed to be associated with favorable clinical development, whereas increasing α4β1 and αEβ7 correlated with negative changes in outcome parameters. Changes in α4β1 integrin expression after six weeks were significantly different in responders and non-responders to vedolizumab therapy as assessed after 16 weeks with a cut-off of +4.2 % yielding 100 % sensitivity and 100 % specificity in ROC analysis. Discussion: Our data show that clinical response to vedolizumab therapy in UC but not in CD is associated with specific changes in integrin expression profiles opening novel avenues for mechanistic research and possibly prediction of response to therapy.